Management of rice blast caused by Magnaporthe oryzae using botanicals, biocontrol agents and organically permitted fungicides - H. KALITA and C. KAPOOR, R. GOPI*, R.K. AVASTHE (Indian Phytopathology, 2016)
Field study was conducted to evaluate the efficacy of biocontrol agents, botanicals and organically approved fungicides in the management of blast disease in rice. Copper oxycholoride @ 0.25% (20.58%, 18.33%) closely followed by copper hydroxide @ 0.25% (21.80%, 20.50%) was found effective in reducing both leaf and neck blast incidence of rice during 2013 and 2014, respectively. Among the biocontrol agents Pseudomonas fluorescens showed maximum disease reduction and increased yield. Among the botanicals, garlic bulb extract and neem oil @ 3% were found effective in reducing the incidence of blast and also increased the yield. Copper fungicides, Pseudomonas fluorescens, botanicals like garlic and neem oil can be used in an integrated way for the management of blast in rice under organic conditions.